Recognition and appropriation of rights among Mayanwomen in the context of a solidarity economy: the case ofthe Solares Collective on the peninsula of Yucatán, Mexico - Fernández-Sarabia, Edwin Alberto; Quintal-López, Rocío Ivonne (Prospectiva. Revista de Trabajo Social e Intervención Social, 2026)
In Latin America, the solidarity economy is proposed as an alternative to prevailing development models, articulating productive practices with cooperation, self-management, and sustainability. In the Yucatán Peninsula, Mayan women play a fundamental role in the family economy and in the transmission of cultural knowledge, generating collective processes that transcend the economic. This study analyzes the experience of the Solares collective organization, established in Sotuta in 2020 during the COVID-19 pandemic, as a self-employment strategy through the recovery of backyard gardens for self-consumption and the marketing of agrochemical-free agricultural products. The research was conducted with a qualitative approach, combining seven months of participant observation and four in-depth interviews with the founders, complemented by narrative analysis using ATLAS.ti 25. The results indicate that participation in Solares fosters subjectivation processes, where women redefine their personal time, access leisure and self-care, and build mutual support networks. At the same time, forms of appropriation and recognition of rights emerge: participants exercise collective deliberation, manage their own resources, and expand their economic and social autonomy, challenging traditional gender norms.